The beats in Mexico - Calonne, David Stephen, 1953- (Rutgers University Press, 2022)
"The Beats in Mexico is the first book to explore the centrality of Mexico in the lives and works of Beat writers. The book surveys not only the already canonized Beat authors such as Lawrence Ferlinghetti, William S. Burroughs, Allen Ginsberg, Jack Kerouac and Michael McClure, but also breaks new ground in its discussion of often -neglected figures such as the great Surrealist poet Philip Lamantia, who made many trips to Mexico. The Beats in Mexico also is innovative due to its emphasis on the female Beats who have not received the scholarly attention they deserve. Calonne devotes individual chapters to Margaret Randall, Bonnie Bremser and Joanne Kyger and demonstrates their importance to the evolution of the Beat movement in their many writings about Mexico as well as in their devotion to exposing the misogyny which characterized both American and Mexican culture in the twentieth century"--